Role of 24-Hour Intraocular Pressure Monitoring in Glaucoma Management - Chun Hing Ho; Jasper K. W. Wong (Journal of Ophthalmology)
Glaucoma is the leading cause of irreversible blindness worldwide and the prevalence is on the rising trend. Intraocular pressure (IOP) reduction is the mainstay of treatment. The current practice of IOP monitoring is based on spot measurements during clinic visits during office hours. However, there are up to 50% of glaucoma patients who had normal initial IOP, while some treated patients continued to have progressive glaucomatous optic nerve damage even with a low IOP. Recent studies have shown that the IOP of glaucoma patients fluctuated during the day with different patterns, and some of them had peak IOP outside office hours. These findings provided us with new insights on the role of 24-hour IOP monitoring in managing normal tension glaucoma and patients with progressive deterioration despite apparently well-controlled IOP. Nevertheless, results to date are rather inconsistent, and there is no consensus yet. In this review, we briefly highlighted the current modalities of 24-hour IOP monitoring and summarized the characteristic 24-hour IOP pattern and the clinical relevance of IOP parameters in predicting glaucomatous progression in different glaucoma subtypes. We also discussed the therapeutic efficacy of current glaucoma treatment modalities with respect to the mentioned 24-hour IOP profiles, so as to strengthen the role of 24-hour IOP monitoring in identifying and stratifying the risks of progression in glaucoma patients, as well as optimizing treatments according to their IOP profiles.